GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 234 species occurrences available in GBIF matching the query: TaxonKey: Paspalum intermedium Munro ex Morong HasCoordinate: true. The dataset includes 234 records from 35 constituent datasets: 1 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1 records from The Fungal Collection at the Botanische Staatssammlung München. 79 records from Instituto de Botánica Darwinion. 3 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 1 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 1 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 11 records from Herbarium of The New York Botanical Garden. 1 records from Herbario Amazónico Colombiano. 20 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 4 records from CESJ - Herbário Leopoldo Krieger. 2 records from ICN - Herbário do Instituto de Ciências Naturais. 4 records from Instituto de Ciencias Naturales. 2 records from Instituto de ciencias naturales. 3 records from VIC - Herbário da Universidade Federal de Viçosa. 9 records from HUEM - Herbário da Universidade Estadual de Maringá. 3 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 1 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 3 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 1 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 8 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 1 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 2 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 1 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 13 records from MBM - Herbário do Museu Botânico Municipal. 2 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from ALCB - Herbário Alexandre Leal Costa. 2 records from Natural History Museum (London) Collection Specimens. 1 records from MBML-Herbario - Herbário Mello Leitão. 2 records from IAC - Herbário do Instituto Agronômico de Campinas. 3 records from United States National Plant Germplasm System Collection. 6 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 33 records from Missouri Botanical Garden. 1 records from UEC - Herbário da Universidade Estadual de Campinas. 3 records from UFMT - Herbário UFMT. 5 records from CPAP - Herbário CPAP.
Keywords: GBIF; biodiversity; species occurrences